Sheikh Mujibur Rahman : Bangladesh, my Bangladesh - Majumdar, Ramendu (Delhi : Orient, 1972)
On Sheikh Mujibur Rahman, 1922-1975, founder of the nation of Bangladesh.
Includes index.
Keywords: Mujibur Rahman, -- Sheikh, -- 1920-1975.; Mujibur Rahman, -- Sheikh, -- 1920-1975; Mujibur Rahman, -- Sheikh, -- 1922-1975.; Politicians -- Bangladesh -- Biography; Ex-presidents -- Bangladesh -- Biography; Political science; Ex-presidents.; Politicians; Bangladesh -- Politics and government; Bangladesh; Bangla Desh; Biography